Yes to nuclear power? Danes’ attitudes towards nuclear power in 1979, 1981 and 2022 - Hedegaard, Troels Fage; Kongshøj, Kristian (Politica, 2025)
Nuclear power has returned to the political agenda in Denmark after being out in the cold since 1985. In this article, we investigate Danes’ attitudes to nuclear power with a survey from 2022 and historical election surveys from 1979 and 1981. The results demonstrate well-known differences across gender and party choice in all years. In 2022, we also find that those who are least worried about climate support nuclear power most. We also find indications of a cohort effect in the sense that Danes who were in their “formative years” when the debate last occurred are more critical of nuclear power. This is most pronounced among climate-concerned and left-wing voters in this age cohort. Opposition to nuclear power from these groups is markedly weaker among the youngest, whose opinions were shaped during a time when nuclear power is being discussed as a solution in climate policy.